Utilization of Petroleum and Natural Gas on the Sustainable Development of Indonesian Economy - Mutiara Maharani; Nabbiel Arbio Akbar (Lembaga Contrarius Indonesia, 2023)
Throughout the history of national development, petroleum and natural gas have played a vital and strategic role, serving as essential energy sources for various economic activities. The petroleum and gas sector also contributes significantly to state revenue through the management of these resources. The author aims to discuss the appropriate utilization of petroleum and natural gas and its potential to enhance economic income in Indonesia. Petroleum and natural gas, as valuable resources, exist in liquid and solid forms within the earth's reservoirs. Indonesia possesses vast reserves of petroleum and gas, with numerous untapped fields remaining. Utilizing these resources effectively can lead to increased state revenue. Given their significance as essential commodities in the national economy, managing petroleum and natural gas is crucial for optimizing prosperity and welfare for the population.